Photosynthesis and water potential of andiroba seedlings submitted to water stress and rewetting - Gonçalves, José Francisco de Carvalho; Silva, Carlos Eduardo Moura da; Guimarães, Diogo Gato (Pesquisa Agropecuaria Brasileira, 2009)
The objective of this work was to investigate the photosynthetic performance of young andiroba plants (Carapa guianensis) submitted to water stress and rewetting. The plants were irrigated daily in greenhouse conditions for 15 days. After acclimatization, the plants were separated randomly in two treatments, irrigated and non-irrigated plants. When the photosynthesis of the non-irrigated plants reached values close to zero, the plants were rewetted. Measurements of gas exchanges and chlorophyll a fluorescence were recorded on seven-day intervals, during 21 days. Plant water potentials were determined at the beginning and at the end of the experiment. Net photosynthesis, stomatal conductance, and transpiration rates were reduced by 88, 89, and 89%, respectively, after 21 days of water stress. In relation to chlorophyll a, fluorescence variables were reduced 27 to 58%. The plant water potential was reduced more than four times by 21 days of stress. With rewetting, seedlings recovered their photosynthetic characteristics in four to eight days as well as their water potential, indicating that young andiroba plants exhibited high physiological plasticity to water stress.
Keywords: Carapa guianensis; water deficit; tree species; chlorophyll a fluorescence; gas exchange